Acquired reactive perforating dermatosis. (29th May 2013) - Wagner, Gunnar; Sachse, Michael Max
Summary: Acquired reactive perforating dermatosis is characterized by umbilicated erythematous papules and plaques with firmly adherent crusts. Histopathological examination shows a typical cup‐shaped ulceration in the epidermis containing cellular debris and collagen. There is transepidermal elimination of degenerated material with basophilic collagen bundles. The etiology and pathogenesis of acquired reactive perforating dermatosis are unclear. Metabolic disorders and malignancies are associated with this dermatosis. Associated pruritus is regarded as a key pathogenic factor. Constant scratching may cause a repetitive trauma to the skin. This pathogenesis may involve a genetic predisposition. The trauma may lead to degeneration of the collagen bundles. Treatment of acquired reactive perforating dermatosis follows a multimodal approach. Apart from the treating any underlying disease, treatment of pruritus is a major goal. Systemic steroids and retinoids, as well as UVB phototherapy are well‐established treatment options. Some patients may also benefit from oral allopurinol.